Verification of Simulated Waves for Statistical Aspects in Zero-Cross Methods - UENO, Kimihiko; HIDA, Yoshinobu (Journal of Fisheries Engineering, 2018)
This study has investigated the difference in wave height frequency distributions caused by thezero-up-cross and zero-down-cross methods for individual waves in a wave-by-wave algorithm. The ratioof the significant wave height to the mean wave height theoretically becomes 1.579 when the waveheight frequency distribution follows the Rayleigh probability density distribution. However, some of thewaves simulated in this study showed values far from the theoretical values. Therefore, in this study, agoodness of fit test was conducted based on the assumption that the wave height frequency distributionfollows the Rayleigh probability density distribution. As a result, several cases showed deviations whencomparing the wave height frequency distribution with the Rayleigh probability density distribution bythe zero-down-cross method but not by the zero-up-cross method.